Sex Difference of Angiotensin IV–, LVV-Hemorphin 7–, and Oxytocin-Induced Antiallodynia at the Spinal Level in Mice With Neuropathic Pain. (June 2018) - Chow, Lok-Hi; Chen, Yuan-Hao; Lai, Chun-Fu; Lin, Tsu-You; Chen, Ying-Jie; Kao, Jen-Hsin; Huang, Eagle Yi-Kung
Abstract : BACKGROUND: We demonstrated previously that angiotensin IV (Ang IV) and LVV-hemorphin 7 (LVV-H7) act through the blockade of insulin-regulated aminopeptidase to decrease oxytocin degradation, thereby causing antihyperalgesia at the spinal level in rats. We determined that intrathecal oxytocin can induce significant antihyperalgesia in male rats with inflammation but not in female rats. Thus, we speculate that Ang IV, LVV-H7, and oxytocin can induce antiallodynia, which could be of great therapeutic potential. Because the antihyperalgesia by using these peptides was with sex difference, their possible antiallodynia was examined in male and female mice for comparison. We investigated whether Ang IV, LVV-H7, and oxytocin produce antiallodynia at the spinal level in mice and whether this antiallodynia differs between the sexes. METHODS: Partial sciatic nerve ligation surgery was performed on adult male and female C57BL/6 mice from the same litter (25–30 g). The effects of intrathecal injections of Ang IV (25.8 nmol), LVV-H7 (27.2 nmol), and oxytocin (0.125 or 1.25 nmol) were assessed through the von Frey test 3 days after partial sciatic nerve ligation. RESULTS: Intrathecal injection of Ang IV, LVV-H7, and oxytocin all produced a potent antiallodynia in male mice. However, these antiallodynia effects were either extremely weak or absent in female mice at the same dose. CONCLUSIONS: Intrathecal Ang IV, LVV-H7, and oxytocin can all cause significant antiallodynia in male mice. The Ang IV-, LVV-H7-, and oxytocin-induced antiallodynia effects differed between the sexes at the spinal level in mice.